Beethoven's "Eroica" Sketchbook - Beethoven, Ludwig van 1770-1827; Lockwood, Lewis 1930-; Gosman, Alan (Illinois University of Illinois Press, 2013)
Among Beethoven's many surviving sketchbooks, one of the most famous is the "Eroica" Sketchbook, containing all the known sketches for the "Eroica" Symphony, the "Waldstein" Sonata, and other works of 180304. These include his first sketches for the opera Leonore (later entitled Fidelio), as well as the unfinished opera Vestas Feuer, the oratorio Christus am Oelberge, the Triple Concerto, songs, keyboard compositions, and early sketches that later bore fruit in the Fourth Piano Concerto and the Fifth and Sixth Symphonies. It also contains ideas for works that were never completed. This edition makes available both a complete facsimile and transcription of the sketchbook for the first time, along with a detailed commentary on the origins, contents, and significance of this vitally important source.
Keywords: 19th Century (1801-1900); Symphony; Musical sketch; Composing; Vienna (Austria)